Facile Engineering of Long‐Term Culturable Ex Vivo Vascularized Tissues Using Biologically Derived Matrices. Issue 23 (23rd October 2018) - Hu, Michael; Dailamy, Amir; Lei, Xin Yi; Parekh, Udit; McDonald, Daniella; Kumar, Aditya; Mali, Prashant
Abstract: Recent advances in tissue engineering and 3D bioprinting have enabled construction of cell‐laden scaffolds containing perfusable vascular networks. Although these methods partially address the nutrient‐diffusion limitations present in engineered tissues, they are still restricted in both their viable vascular geometries and matrix material compatibility. To address this, tissue constructs are engineered via encapsulation of 3D printed, evacuable, free standing scaffolds of poly(vinyl alcohol) (PVA) in biologically derived matrices. The ease of printability and water‐soluble nature of PVA grant compatibility with biologically relevant matrix materials and allow for easily repeatable generation of complex vascular patterns. This study confirms the ability of this approach to produce perfusable vascularized matrices capable of sustaining both cocultures of multiple cell types and excised tumor fragments ex vivo over multiple weeks. The study further demonstrates the ability of the approach to produce hybrid patterns allowing for coculture of vasculature and epithelial cell‐lined lumens in close proximity, thereby enabling ex vivo recapitulation of gut‐like systems. Taken together, the methodology is versatile, broadly applicable, and importantly, simple to use, enabling ready applicability in many research settings. It is believed that this technique has the potential to significantly accelerate progress in engineering and study of ex vivo organotypic tissue constructs. Abstract : Vascularized tissue constructs are produced from a variety of biological matrix substitutes via 3D printing of evacuable poly(vinyl alcohol) scaffolds. This technique generates perfusable constructs with complex vascular geometries. Experimental studies reveal that the constructs are capable of long‐term sustenance of tumor tissue ex‐vivo, and allow for production of hybrid gut‐like organoid systems containing both epithelial and endothelial cells.